2006
DOI: 10.1051/0004-6361:20053710
|View full text |Cite
|
Sign up to set email alerts
|

Active galactic nuclei in the mid-IR

Abstract: Aims. We study the evolution of the luminosity function (LF) of type-1 and type-2 Active Galactic Nuclei (AGN) in the mid-infrared, derive the contribution of the AGN to the Cosmic InfraRed Background (CIRB) and the expected source counts to be observed by Spitzer at 24 µm. Methods. We used a sample of type-1 and type-2 AGN selected at 15 µm (ISO) and 12 µm (IRAS), and classified on the basis of their optical spectra. Local spectral templates of type-1 and type-2 AGN have been used to derive the intrinsic 15 µ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
111
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 64 publications
(132 citation statements)
references
References 70 publications
20
111
0
Order By: Relevance
“…Gruppioni et al 2005;Le Floc'h et al 2005;Pérez-González et al 2005;Babbedge et al 2006;Caputi et al 2007). On the contrary, the evolution of AGN at MIR wavelengths are similar to what has been measured in the optical and X-ray bands for type 1 AGN (AGN1) and even slower for type 2 AGN (Matute et al 2002(Matute et al , 2006.…”
Section: Introductionsupporting
confidence: 81%
See 4 more Smart Citations
“…Gruppioni et al 2005;Le Floc'h et al 2005;Pérez-González et al 2005;Babbedge et al 2006;Caputi et al 2007). On the contrary, the evolution of AGN at MIR wavelengths are similar to what has been measured in the optical and X-ray bands for type 1 AGN (AGN1) and even slower for type 2 AGN (Matute et al 2002(Matute et al , 2006.…”
Section: Introductionsupporting
confidence: 81%
“…3). In contrast, all the newly classified AGN2 have IR luminosities in the range 10 9.5 L < L 15 < 10 11 L , exactly in the region of the AGN2 LF where a flattening has been observed (Matute et al 2006). This result confirms the hypothesis of Matute et al (2006) that the observed flattening of the AGN2 LF at redshift ∼0.35 was due to an incompleteness in the AGN identification.…”
Section: The Newly Classified Agnsupporting
confidence: 73%
See 3 more Smart Citations